Discomfort and Other Factors that Influence the Effectiveness of Graduate Student Peer Consultations - Krisztina Erzsebet Dearborn; Mark W Pleiss (To Improve the Academy, 2021)
The following study reports the findings of two surveys given to graduate teacher consultants (n = 30) and graduate student teachers (n = 59) who completed video-teacher consultations at a public, R1 university. The surveys assessed the overall effectiveness of peer consultation for both sides and identified the factors that influenced those assessments. We found that the level of comfort expressed by consultants and graduate teachers during their first consultations had the greatest impact on their perceived level of effectiveness. The time between consultants’ training and their first consultation also affected their assessments. Other factors that did and did not influence the consultation are also discussed, along with recommendations and best practices learned from our surveys.